THE CONCEPT “MEDIA TEXT” IN LINGUISTIC STUDIES - Karbozova Gulnara Kumisbekovna; Ordabek B.O. (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article constitutes a critical review of modern and widespread term such as media text and its distinctive peculiarities and aspects it covers. The works and expressions of well-known linguists and scientists, both domestic and foreign, in media sphere are noted. The general aim is to show what’s role of media texts in the contemporary world and in what way it affects to people’ mind and their view to the globe. We have provided a few examples of media texts with their translations from English to Russian and Kazakh languages and analyzed them from the translation point of view and showed what translation methods and techniques were used. We identified the main topics in media sphere in several countries and distinguished the target audience of each media product in television channels and radio as well as the key characters in media texts. It is concluded that rapidly developing phenomenon of media text is increasingly being investigated in modern linguistics.